divining INTOXICATION - Sinner, Anita (Canadian Journal of Education/Revue canadienne de l’éducation, 2002)
Video available on YouTube: https://youtu.be/nwyFGVeBcuc TO INQUIRE, A/R/TOGRAPHICALLY Arts-based inquiry offers a range of methods to engage in the process of questioning, reflecting, and doing. A/r/tography, an emerging school of thought based in Art Education/Curriculum Studies at the University of British Columbia, is one such dynamic approach to qualitative research that challenges our notions and helps move our thinking forward as artists, researchers, and teachers. A/r/tography is defined as: To be engaged in the practice of a/r/tography means to inquire in the world through an on going process of art making and writing not separate or illustrative of each other butinterconnected and woven through each other to create additional and/or enhancedmeanings. A/r/tographical work is rendered through the methodological concepts of contiguity, living inquiry, openings, metaphor/metonymy, reverberations and excess which are enacted and presented/performed when a relational aesthetic inquiry approach is envisioned as embodied understandings and exchanges between art and text, and between and among the broadly conceived identities of artist/researcher/teacher. A/r/tography is inherently about self as artist/researcher/teacher yet it is also social when groups or communities of a/r/tographers come together to engage in shared inquiries, act as critical friends, articulate an evolution of research questions, and present their collective evocative/provocative works to others. (R. Irwin, personal communication, June 12, 2004)